ANALISIS PROFIL USAHA EKONOMI DESA SIMPAN PINJAM (UED SP) BIDANG PENGEMBANGAN USAHA MIKRO DAN KECIL (UMK) DI DESA BANTAN TENGAH KECAMATAN BANTAN KABUPATEN BENGKALIS - Rini Arvikasari; Erma Domos (Inovbiz: Jurnal Inovasi Bisnis, 2018)
This research aims to determine how the difference of sales turnover and advantages of UMK before and after receiving the grant of capital loan credit from REE-SL Business Development.This research is a qulitative descriptive.. Data collection techniques used questionnaire and observation to obtain data on SME development before and after receiving the loan capital grants of REE-SL Business Development. The results show that: (1) There are differences between the turnover of sales before and after receiving the loan capital grants of REE-SL Business Development. (2) There are differences in profit before and after receiving the loam capital grants from UED- SP Business Development.